Employment issues among Malaysian information and communication technology (ICT) graduates: a case study - Ramakrishnan, K.; Yasin, N.M. (2012)
In the 21st Century, there has been a growing concern about the role of higher education institution and how well they are satisfying the employers' needs. Malaysian Prime Minister mentioned that only 23 of the workforce is highly skilled in year 2010. This percentage is much lower compared to other developed countries. It was stressed that, there is a need to improve the composition of highly skilled workers to at least 37 by 2015, to become a developed nation. The purpose of this paper is to highlight the causes of unemployment among ICT graduates in Malaysia and the need for changes in the curriculum. Data were collected based on quantitative and qualitative study. Questionnaires were used to gather information from 296 current undergraduate students and 248 graduated students. These students are from public University in Malaysia. Besides distributing questionnaires, short interviews were also carried out. This paper concludes that the higher education institutions need to reengineer their curriculum in order to keep them updated in-line with employers need in the job market.